2013
DOI: 10.1186/1746-6148-9-226
|View full text |Cite
|
Sign up to set email alerts
|

A fully caninised anti-NGF monoclonal antibody for pain relief in dogs

Abstract: Background: Monoclonal antibodies are a major class of biological therapies in human medicine but have not yet been successfully applied to veterinary species. We have developed a novel approach, PETisation, to rapidly convert antibodies for use in veterinary species. As an example, anti-nerve growth factor (anti-NGF) monoclonal antibodies (mAbs) which are effective in reducing acute and chronic pain in rodents and man are potentially useful for treating pain in dogs but a fully caninised mAb is required in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…To our knowledge, this is the first report comparing the in vivo behavior of different canine isotypes. While the exact mechanism(s) of B-cell depletion by the 1E4-cIgGB and 1E4-cIgGC anti-CD20 antibodies we have developed in this study are under investigation, our B-cell depletion and CD16a binding results are consistent with the findings of recent reports of in vitro characterization of the four canine isotypes; these studies also found that only cIgGB and cIgGC are able to engage receptors involved in ADCC and CDC (Bergeron et al, 2014;Gearing et al, 2013) Together, these findings should pave the way for custom design and engineering of canine biologics.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the first report comparing the in vivo behavior of different canine isotypes. While the exact mechanism(s) of B-cell depletion by the 1E4-cIgGB and 1E4-cIgGC anti-CD20 antibodies we have developed in this study are under investigation, our B-cell depletion and CD16a binding results are consistent with the findings of recent reports of in vitro characterization of the four canine isotypes; these studies also found that only cIgGB and cIgGC are able to engage receptors involved in ADCC and CDC (Bergeron et al, 2014;Gearing et al, 2013) Together, these findings should pave the way for custom design and engineering of canine biologics.…”
Section: Discussionsupporting
confidence: 93%
“…To decrease the immunogenic potential of rat anti‐mouse NGF mAb αD11 in the cat, while retaining its high affinity for NGF, amino acid substitutions were made to the heavy and light chain variable domain framework sequences by alignment with a collection of predicted protein sequences encoded by expressed feline immunoglobulin (IgG) complementary deoxyribonucleic acid (cDNA) sequences. This approach (that we refer to as PETization) previously was used to generate a fully caninized anti‐NGF mAb that has a promising efficacy and safety profile in dogs . Where an amino acid in the αD11 sequence corresponded to an amino acid in the collection no change was made.…”
Section: Methodsmentioning
confidence: 99%
“…Plates were coated with 2.5 μg/mL mouse NGF and blocked with 5% bovine serum albumin (BSA)/phosphate‐buffered saline (PBS). Coated wells were incubated for 1 hour at room temperature with NV‐02 antibody, or as a positive control a caninized anti‐NGF mAb with a IgG‐B isotype (complement‐binding) heavy chain, diluted in PBS/1% BSA. Antibody concentrations ranged from 10 μg/mL to 1.0 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations